Transport of proteins to the mitochondrial intermembrane space: the 'matrix-targeting' and the 'sorting' domains in the cytochrome c1 presequence. - van Loon, A P (1987)
We reported earlier that the yeast cytochrome c1 presequence (length: 61 amino acids) directs attached proteins to the mitochondrial intermembrane space and that it appears to contain two functional domains: a 'matrix-targeting' domain, and a 'sorting' domain. We have now used gene manipulation together with two different in vivo import assays to map these two domains within the cytochrome c1 presequence. The 'matrix-targeting' domain is contained within the N-terminal 16 residues (or less); by itself, it directs attached proteins to the matrix. The 'sorting' domain extends into the C-terminal 13 residues of the presequence; while it does not mediate intracellular protein transport by itself, it acts together with the preceding 'matrix-targeting' sequence in sorting attached proteins into the intermembrane space. On replacing the authentic 'matrix-targeting' sequence with artificial sequences of different lengths we found that sorting of proteins between the outer membrane and the intermembrane space is not exclusively determined by the length of the N-terminal 'matrix-targeting' sequence.